ANALISIS TATA LETAK FASILITAS PRODUKSI KOPI MENGGUNAKAN METODE CRAFT (Studi Kasus PT Mulyaningsih Jember) - Ramadhan, Rizqi Dhia; Mahardika, Nidya Shara; Purnomo, Bambang Herry; Suryaningrat, Ida Bagus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2025)
ABSTRACT Layout design is a process that involves ways to improve the layout of an industrial company so that the layout used is more efficient and optimal during production. The layout design in this study aims to compare the layout in coffee production using the CRAFT method and the ARC method, to optimize the production flow at PT Mulyaningsih. The application of the CRAFT method obtained the results of 1 iteration where there was a transfer of the green pump department (8) and the mason department (9), the transfer obtained the result of reducing the material handling distance with a distance difference of 18 m with an efficiency of 3.27% and a reduction in material handling costs with a cost difference of Rp 1,022,400 with an efficiency of 6.16%. The application of the ARC method obtained the result of the inconsistency of the degree of proximity with the description of the reason between the rinsing tub department (7) and the mason (9) which should be the rinsing tub department (7) to the green pump department (8) which has an absolute relationship according to the workflow sequence, so that there is a displacement between the green pump department and the mason department to match the degree of proximity relationship. Therefore, comparing the CRAFT method and the resulting ARC method is straightforward, where both the green pump department and the mason department are moved from the data input carried out in the CRAFT method and strengthened by the ARC method, with a close relationship between them.